2SPD-007 Comparative effectiveness and safety of everolimus and axitinib as second-line therapy in metastatic renal cell carcinoma. (2nd March 2018) - Collado-Borrell, R; Escudero-Vilaplana, V; Ortega-Navarro, C; García-Martín, E; Herranz-Alonso, A; Sanjurjo-Saez, M
Abstract : Background: Both everolimus and axitinib are approved for patients with metastatic renal cell carcinoma (mRCC) in second-line therapy. Currently, there are no comparative clinical trials reported. Purpose: The objective of this study is to assess the effectiveness and safety of everolimus vs axitinib for Tyrosine-Kinase Inhibitors (TKI) refractory mRCC patients in clinical practice. Material and methods: A comparative study was conducted retrospectively. Patients treated with everolimus or axitinib for TKI refractory mRCC from June 2014 to 2016 were included. Variables were recorded: age, ECOG, line and duration of the treatment, reason and date of progression, adverse effects (AE) and dose reductions. Effectiveness was evaluated in terms of Progression Free Survival (PFS) measured from the beginning of treatment until its interruption for progression or death, according to RECIST v. 1. 1. Safety was evaluated according to AE profile from the criteria CTCAE v4. 03 and dose reductions. Data analysis was performed using the statistical program PASW18. PFS was compared between everolimus-axitinib using multivariable Cox proportional hazards regression models. Results: We analysed 31 patients: everolimus (n=16) vs axitinib (n=15). The mean age was 64.2 years (SD:14.1). ECOG was respectively: 0 (46.7% vs 73.3%), 1 (33.3% vs 13.3%), not available (20% vs 13.4%). The lines of treatment were respectively: 2° (56.3%; 66.7%), ≥3ª (43.7%; 33.3%). The median duration of treatment (days) was: 207 (55–657) vs 255 (28–547). Effectiveness (everolimus vs axitinib): the median of PFS was: 7.1 months (95% CI: 4.6 to 10) vs 9.4 months (95% CI: 6.2 to 12.9). HR=0. 86; p=0.13. Reasons for treatment interruption were: progression (87.5% vs 86.7%) and exitus (12.5% vs 13.3%). Safety: 71% of the patients presented AE (68.9% everolimus vs 73/3% axitinib). The most frequent were: rash (31.3% vs 20%), stomatitis (25% vs 20%) and hypothyroidism (0% vs 40%). Serious AE (grade ≥3): asthaenia (6.3% vs 0%) and rash (6.3% vs 0%). The dose was reduced in 50% vs 13.3% patients. Conclusion: No significant difference in PFS was observed between everolimus and axitinib for ITK refractory mRCC patients. However, axitinib appears to provide more PFS. Regarding the safety profile, AE were frequent in both treatments but was more serious with everolimus. Everolimus required more dose reductions. References and/or Acknowledgements: 1. PMID: 28888866. 2. PMID: 26744781. No conflict of interest